2015
DOI: 10.1051/swsc/2015023
|View full text |Cite
|
Sign up to set email alerts
|

Long-term comparison of the ionospheric F2 layer electron density peak derived from ionosonde data and Formosat-3/COSMIC occultations

Abstract: Electron density profiles (EDPs) derived from GNSS radio occultation (RO) measurements provide valuable information on the vertical electron density structure of the ionosphere and, among others, allow the extraction of key parameters such as the maximum electron density NmF2 and the corresponding peak height hmF2 of the F2 layer. An efficient electron density retrieval method, developed at the UPC (Barcelona, Spain), has been applied in this work to assess the accuracy of NmF2and hmF2 as determined from Formo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Moreover, these observations of the EIA crests are in the winter months of October-December; the transequatorial neutral winds blowing across the summer-winter hemisphere might have possibly pushed the EIA to latitudes as high as Allahabad (Luan et al, 2015). Our results on the observations of EIA are in reasonable agreement with some of the earlier reports (Rao and Malhotra, 1964;Rama Rao et al, 1977;Lin et al, 2007;Chakraborty and Hajra, 2009;Zhao et al, 2009). Studies by Rao and Malhotra (1964) on the latitudinal variation of foF2 in the Asian sector suggest that the EIA can persist at least until 02:00 LT at ∼ 30 • dip latitude.…”
Section: Nocturnal Behaviour Of Nm: Signatures Of Eia and Mtmsupporting
confidence: 93%
See 3 more Smart Citations
“…Moreover, these observations of the EIA crests are in the winter months of October-December; the transequatorial neutral winds blowing across the summer-winter hemisphere might have possibly pushed the EIA to latitudes as high as Allahabad (Luan et al, 2015). Our results on the observations of EIA are in reasonable agreement with some of the earlier reports (Rao and Malhotra, 1964;Rama Rao et al, 1977;Lin et al, 2007;Chakraborty and Hajra, 2009;Zhao et al, 2009). Studies by Rao and Malhotra (1964) on the latitudinal variation of foF2 in the Asian sector suggest that the EIA can persist at least until 02:00 LT at ∼ 30 • dip latitude.…”
Section: Nocturnal Behaviour Of Nm: Signatures Of Eia and Mtmsupporting
confidence: 93%
“…Because of this [O 2 ] association, the intensity of OI 630.0 nm (I 6300 ) depends upon the height of the F layer apart from the electron density. Link and Cogger (1988) found that the intensity of this emission depends on [N 2 ] and [O 2 ] of the neutral atmosphere. As the density of the neutral atmosphere decreases exponentially with height around the OI 630.0 nm emission altitude, such dependency is also likely to exist between its intensity and the height of the F layer.…”
Section: Nm and Hmfmeasurements: Underlying Theory Assumptions And Lmentioning
confidence: 98%
See 2 more Smart Citations
“…As the ionizing radiation from the sun penetrates deeper and deeper into the Earth's atmosphere, it encounters a larger and larger density of gas particles, producing more and more electrons per unit volume (Bittencourt 2004). The recombination of free electrons with positive ions is a reversion of the photoionization and the recombination process is the main driver to produce neutral atoms (Limberger et al 2015).…”
Section: Introductionmentioning
confidence: 99%